2020
DOI: 10.1155/2020/8866559
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Stage Failure Mechanism and Stability Control of Surrounding Rock of Repeated Mining Roadway

Abstract: China is one of the leading countries in the mining and utilization of coal resources, and the problems of coal-mining technology and safety have been concerned by the world, while the serious deformation and destruction of surrounding rock and the difficulty of support have brought inconvenience to the mining of coal resources due to repeated mining. This paper takes the actual engineering 22205 mining roadway in Buertai mine as the research background, through the combination of numerical simulation and fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Yuan and Zhu used a numerical simulation method to study the evolution of the surrounding rock stress under the condition of overlapping coal pillar and mining action. Through the simulation results of the back mining process, it was verified that the deformation and failure of the surrounding rock is the result of the combined action of lateral bearing pressure of the adjacent working face, leading bearing pressure, and stress transfer from the overlapping coal pillar 3‐6 . Yu analyzed the action mechanism of strong mine pressure in a working face in the conditions of multi‐seam mining disturbance and coal pillar influence, and through theoretical analysis and field measurements calculated the depth and range of the stress concentration area 7‐9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan and Zhu used a numerical simulation method to study the evolution of the surrounding rock stress under the condition of overlapping coal pillar and mining action. Through the simulation results of the back mining process, it was verified that the deformation and failure of the surrounding rock is the result of the combined action of lateral bearing pressure of the adjacent working face, leading bearing pressure, and stress transfer from the overlapping coal pillar 3‐6 . Yu analyzed the action mechanism of strong mine pressure in a working face in the conditions of multi‐seam mining disturbance and coal pillar influence, and through theoretical analysis and field measurements calculated the depth and range of the stress concentration area 7‐9 .…”
Section: Introductionmentioning
confidence: 99%
“…Through the simulation results of the back mining process, it was verified that the deformation and failure of the surrounding rock is the result of the combined action of lateral bearing pressure of the adjacent working face, leading bearing pressure, and stress transfer from the overlapping coal pillar. [3][4][5][6] Yu analyzed the action mechanism of strong mine pressure in a working face in the conditions of multi-seam mining disturbance and coal pillar influence, and through theoretical analysis and field measurements calculated the depth and range of the stress concentration area. [7][8][9] Zhang and He et al analyzed the influence of different coal pillars on the stress superposition of the lower coal roadway and showed that the mining disturbance-induced stress superposition of the adjacent coal seams had a strong impact on roadway stability.…”
mentioning
confidence: 99%
“…For a long time, academics have always believed that the shape of the plastic zone around a circular hole is circular or elliptical [11], which is suitable for tunnel engineering excavated under isobaric or low-pressure stress conditions but has been proven to be unsuitable in tunneling projects disturbed by high bias stresses [12,13]. Ma Nianjie [14] et al proposed the "*" distribution of the surrounding rock plastic zone for the mining roadway.…”
Section: Introductionmentioning
confidence: 99%
“…Ma Nianjie [14] et al proposed the "*" distribution of the surrounding rock plastic zone for the mining roadway. After that, the team obtained the implicit equation of the surrounding rock plastic excavated under isobaric or low-pressure stress conditions but has been proven to be unsuitable in tunneling projects disturbed by high bias stresses [12,13]. Ma Nianjie [14] et al proposed the " * " distribution of the surrounding rock plastic zone for the mining roadway.…”
Section: Introductionmentioning
confidence: 99%
“…ere are also abundant research results relating to the deformation and failure characteristics of rock structures surrounding roadways [17][18][19][20][21][22][23][24]. Li et al [25] used a numerical simulation method to study the mechanism of roadway failure caused by repeated caving in the Huaibei mining area and proposed a new supporting scheme.…”
Section: Introductionmentioning
confidence: 99%